Study Analysis of the Effectiveness of Using the Digital Al-Quran among College Students in the Dimensions of Globalization Flow - Fahril Husaeni; Zainal Arifin; Ajat Rukajat; Fadhil Santosa (Jurnal al-Thullab, 2021)
Abstract: The current globalization has a significant impact on the spiritual values, mindset, and attitude of the millennial generation, especially in universities in Indonesia. It takes serious efforts from educational practitioners to stem the negative impact of the changing times. one of them is how to encourage students to further increase the intensity of their interactions with the Koran. The presence of the Digital Al-Quran Application can be an alternative, practical and efficient solution to strengthen the motivation of the millennial generation to seek essential spiritual sources. This study aims to measure the effectiveness of using the Digital Al-Quran among students in tertiary institutions in the increasingly sharp dimensions of globalization. The research method used a quantitative approach by applying an analytic descriptive study. Using a random sampling technique, participants were drawn from 71 respondents to the Counseling Guidance student at the third level. The scoring pattern uses the Guttman scale framework. The study results showed an increase in the effectiveness of 53.5% in reading the Al-Quran, and 92.9% of the majority agreed that the Digital Al-Quran application made it easier for students to interact more intensely with the Al-Quran. Besides that, 57.7% of students stated that the Digital Al-Quran was one of the main motivations for renovating their worship. The influence of globalization does not seem to discourage students from instilling their love for emotional relationships with the Koran through digital applications. Abstrak: Arus globalisasi berdampak signifikan terhadap nilai-nilai spiritualitas, pola pikir dan attitude para generasi millennial khususnya di Perguruan Tinggi di Indonesia. Diperlukan upaya-upaya serius dari para praktisi pendidikan dalam rangka membendung dampak negative dari perubahan zaman tersebut. salah satunya adalah bagaimana mendorong para mahasiswa untuk lebih meningkatkan intensitas interaksi mereka Bersama Al-Quran. Kehadiran Aplikasi Al-Quran Digital dapat menjadi salah satu solusi alternatif, praktis dan efisien dalam rangka menguatkan dorongan generasi millennial untuk mencari sumber-sumber spiritual esensial. Penelitian ini bertujuan untuk mengukur efektivitas penggunaan Al-Quran Digital di Kalangan Mahasiswa di Perguruan Tinggi dalam dimensi arus globalisasi yang semakin tajam. Metode Penelitian menggunakan pendekatan kuantatif dengan menerapkan studi deskriptif analitik. Menggunakan teknik random sampling, partisipan di ambil dari 71 responden mahasiswa Bimbingan Konseling pada tingkat ketiga. Adapun Pola skor menggunakan kerangka skala Guttman. Hasil Studi menunjukkan adanya peningkatan efektivitas sebesar 53,5% dalam membaca Al-Quran, serta 92,9% mayoritas sepakat aplikasi Al-Quran Digital sangat memudahkan mahasiswa untuk lebih intens berinteraksi dengan Al-Quran. Disamping itu, 57,7% mahasiswa menyatakan bahwa Al-Quran Digital menjadi salah satu motivasi utama dalam merenovasi ibadah mereka. Pengaruh globalisasi rupanya tidak menurunkan semangat para mahasiswa untuk menanamkan kecintaan mereka dalam melakukan hubungan emosional dengan Al-Quran melalui aplikasi digital.